1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Why does a = -a?

  1. Oct 16, 2014 #1
    I've been messing around with numbers (as you do) and I'm wondering why this occurs..
    lets let a = b-c.
    √a
    = √(b-c)
    =√(-(c-b))
    =i√(c-b)
    =i√(-(b-c))
    =i2√(b-c)
    =-√(b-c)
    =-√a
    For example if you let a = 1, b = 2, and c = 1.
     
  2. jcsd
  3. Oct 16, 2014 #2

    Mark44

    Staff: Mentor

    The step above is where the problem is. You're using the property that ##\sqrt{ab} = \sqrt{a}\sqrt{b}##
    There are restrictions on this and some of the other square root properties - both a and b have to be nonnegative.
     
    Last edited: Oct 16, 2014
  4. Oct 16, 2014 #3
    That makes sense. Thanks.
     
  5. Oct 18, 2014 #4

    FactChecker

    User Avatar
    Science Advisor
    Gold Member

    [itex]\sqrt[2]{-1} = \pm i. [/itex] The choice of the '+' or '-' depends on the situation. So your result is '[itex] a = \pm a [/itex]' where you must decide which sign is correct.
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook




Similar Discussions: Why does a = -a?
  1. Why does E=MC2? (Replies: 18)

  2. Why does this work? (Replies: 4)

Loading...